2015
DOI: 10.1007/s11630-015-0761-7
|View full text |Cite
|
Sign up to set email alerts
|

An airfoil parameterization method for the representation and optimization of wind turbine special airfoil

Abstract: A new airfoil shape parameterization method is developed, which extended the Bezier curve to the generalized form with adjustable shape parameters. The local control parameters at airfoil leading and trailing edge regions are enhanced, where have significant effect on the aerodynamic performance of wind turbine. The results show this improved parameterization method has advantages in the fitting characteristics of geometry shape and aerodynamic performance comparing with other three common airfoil parameteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Defined as a set of control points that allows representation of a complete geometry, in a generalized way the method is extended to a series of polynomials of different order according to the number of control points, the order being equal to n-1 control points of each curve. But this method has disadvantages such as the global change of the geometry due to the single movement of a point, even that characteristic is named "one movement, hundreds of movements" [14]. According to [15] Bezier curve is defined by the equation for given control points and Bernstein polynomials…”
Section: Parameterization Methodsmentioning
confidence: 99%
“…Defined as a set of control points that allows representation of a complete geometry, in a generalized way the method is extended to a series of polynomials of different order according to the number of control points, the order being equal to n-1 control points of each curve. But this method has disadvantages such as the global change of the geometry due to the single movement of a point, even that characteristic is named "one movement, hundreds of movements" [14]. According to [15] Bezier curve is defined by the equation for given control points and Bernstein polynomials…”
Section: Parameterization Methodsmentioning
confidence: 99%
“…Although there has been extensive work in optimizing an aircraft OML to improve overall performance, most methods have one or more of the following drawbacks: (i) no structural constraints are considered when defining geometry (Tandies and Assareh 2016;Lane and Marshall 2009;Liem et al 2017), (ii) no analytical C 1 geometric representation exists (Liem et al 2017;Morris et al 2010), and/or (iii) the design is optimized for only a limited number of flight conditions Tandies and Assareh 2016;Lane and Marshall 2009;Liem et al 2017;Liu et al 2015;Hicks and Henne 1978). Optimized configurations that do not consider (i) will result in thin airfoils that are infeasible to manufacture while drawback (ii) hinders the use of gradient-based methods or sensitivity analyses and results in high-drag OMLs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Menon et al performed a structural optimization of the airfoil trailing edge slotting for the NACA 64(3)-618 and DU93-W-210 airfoils and analyzed the influence of trailing edge slotting on the blade aerodynamic load [10]. Liu et al established a parametric airfoil design method that was applied to DU93-W-210 airfoil optimization and found that this method had better convergence speed than the traditional design method [11]. Moreover, Henriques et al applied the inverse design method to airfoil optimization [12].…”
Section: Introductionmentioning
confidence: 99%